Farmer story: crop rotation and diversification - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
Farmer Samuel Ombati from the Nyando climate-smart villages explains all about crop rotation and diversification on his farm. Video is part of a series highlighting simple technologies farmers are adopting to adapt to the changing climate. More information on CCAFS work in East Africa: ccafs.cgiar.org/regions/east-africa